PROFESSOR K.QURAMBAEVTÍŃ ÁDEBIY BAYLANÍSLARDÍŃ RAWAJLANÍWÍNA QOSQAN ÚLESI - Ametova, Muxabbat Orazimbetovna (ILIM hám JÁMIYET, 2026)
The article discusses the creative path of the renowned Uzbek scholar K.Quramboyev, his role in the literary relations of the Turkic peoples, and the significance of his sciyentific works.